Individual and Interactive Temporal Implications of UV-B Radiation and Elevated CO2 on the Morphology of Basil (Ocimum basilicum L.) - T. Casey Barickman (MDPI AG, 2021)
Temporal and spatial variations in ozone levels and temporal changes in solar radiation greatly influence ultraviolet radiation incidence to crops throughout their growth, yet the interactive effects of CO2 and UV-B radiation on Basil production under sunlight environmental conditions has not been studied. Basil ‘Genovese’ plants grown under sunlit plant growth chambers were subjected to a combination of supplemental UV-B (0 and 10 kJ m−2d−1) and ambient (420 ppm) and elevated (720 ppm) CO2 treatments for 38 days after 14 days of germination. UV-B radiation treatments caused a decrease in basil stem branching, fresh mass, and stem dry mass under both CO2 treatments when harvested after 17 and 38 days of treatment. There was also an increase in basil leaf surface wax under UV-B (10 kJ m−2d−1) treatment compared to controls (0 kJ m−2d−1). Elevated CO2 treatments caused a decrease in morphological features, including specific leaf area and fresh mass. Interactive effects between UV-B and CO2 treatments existed for some morphological features, including plant height, root surface area, and average root diameter. Understanding the impacts that CO2 and UV-B radiation treatments have on basilcan improve existing varieties for increased tolerance while simultaneously improving yield, plant morphology, and physiology.